Nasal Cytology: A Easy Diagnostic Tool in Precision Medicine for Inflammation in Epithelial Barrier Damage in the Nose. A Perspective Mini Review - Caruso, Cristiano; Giancaspro, Rossana; Guida, Giuseppe; Macchi, Alberto; Landi, Massimo; Heffler, Enrico; Gelardi, Matteo (Frontiers in Allergy, 2022)
Nasal cytology is a diagnostic tool that can be used in precision rhinology medicine. Particularly in non-allergic rhinitis and chronic rhinosinusitis forms it can be useful to evaluate biomarkers of both surgical or biological therapy and especially in the follow-up it must be used to predict the prognostic index of recurrence of nasal polyposis. All inflammatory cytokines are also linked to the presence of cells such as eosinophils and mastcells and nasal cytology is a non-invasive and repeatable method to assess the situation in real life.